Peran Organisasi Mahasiswa dalam Meningkatkan Kemampuan Komunikasi Interpersonal yang Efektif - Aulia, Fadila; Dwianggraeni, Putri Rahma; Ishak, Ahmad Raihan (Program Studi Ilmu Komunikasi UII, 2023)
Student organizations on campus have an important role in improving students' soft skills and hard skills. One of the abilities that can be improved through organizations is interpersonal communication skills. This research examines the role of student organizations in improving effective interpersonal communication skills among students who are active in organizations. The research uses a qualitative approach with a phenomenological strategy. The research subjects were students who were active in organizations at the Universitas Islam Indonesia. The research results show that organizations have a big influence in improving students' communication skills. The informants interviewed in this research stated that organizational experience increased not only self-confidence, but also communication skills. The informants also stated that they had become more open to other parties in communicating. Organizational communication experience, especially small group communication, seems to make a significant contribution in improving their interpersonal communication.